Theories of knowledge - "O'neill, Reginald F." (New Jersey, 1963)
This book presents an introductory study of human knowledge which is positive rather than polemical in its approach, adequate both in the number of topics discussed and in he individual analyses, and indicative of the richness of the content of a philosophical realism.
Keywords: "Human Knowledge : knowledge,Theories of"